2001
DOI: 10.1097/00001756-200105080-00034
|View full text |Cite
|
Sign up to set email alerts
|

Upper/lower visual field asymmetry on a spatial relocation memory task

Abstract: The purpose of this study was to investigate whether the lower visual field advantage reported on a number of visual tasks depends on the activity of neural systems which process information from different spaces. To this end, a double dissociation logic was followed by observing the effects of visual and spatial interference on a relocation memory task performed by 80 volunteers. Results showed that participants were better at relocating stimuli presented in the lower than in the upper visual field. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…In recent years, the theoretical and methodological marriage of cognitive psychology and cognitive neurosciences has led to a re-evaluation of the role of action systems in information processing: task demands and action requirements have been found to affect visual perception (Craighero, Fadiga, Rizzolatti, & Umilta`, 1999;Hamilton, Joyce, Flanagan, Frith, & Wolpert, 2005;Mu¨sseler & Hommel, 1997;Wohlschla¨ger, 2000), the selection of visual objects (Hommel & Schneider, 2002;Lupia´n˜ez, Ruz, Funes, & Milliken, 2005;Rizzolatti, Riggio, & Sheliga, 1994;Tipper, Howard, & Houghton, 1999), and memory (Genzano, Di Nocera, & Ferlazzo, 2001;Hommel & Knuf, 2000;Pickering, Gathercole, Hall, & Lloyd, 2001), suggesting a more dynamic interplay between action control and other cognitive systems than the standard unidirectional stage model of human information processing suggests (Ward, 2002). However, despite the increase of empirical evidence, the nature and functional meaning of these interactions are still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the theoretical and methodological marriage of cognitive psychology and cognitive neurosciences has led to a re-evaluation of the role of action systems in information processing: task demands and action requirements have been found to affect visual perception (Craighero, Fadiga, Rizzolatti, & Umilta`, 1999;Hamilton, Joyce, Flanagan, Frith, & Wolpert, 2005;Mu¨sseler & Hommel, 1997;Wohlschla¨ger, 2000), the selection of visual objects (Hommel & Schneider, 2002;Lupia´n˜ez, Ruz, Funes, & Milliken, 2005;Rizzolatti, Riggio, & Sheliga, 1994;Tipper, Howard, & Houghton, 1999), and memory (Genzano, Di Nocera, & Ferlazzo, 2001;Hommel & Knuf, 2000;Pickering, Gathercole, Hall, & Lloyd, 2001), suggesting a more dynamic interplay between action control and other cognitive systems than the standard unidirectional stage model of human information processing suggests (Ward, 2002). However, despite the increase of empirical evidence, the nature and functional meaning of these interactions are still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in extrastriate cortex, the LVF is represented dorsally and the UVF ventrally [4,5] . Behaviorally, LVF superiority has been found across a variety of tasks: simple reaction time [6] , luminance threshold [7] , temporal and spatial contrast sensitivities and visual acuity [3] , perception of illusory contours [8] , sensitivity to chromatic motion under isoluminant conditions [9] , visually guided pointing [10] and spatial relocation memory task [11] . Moreover, some behavioral studies suggest that there might be attentional asymmetry between the upper and lower visual fields.…”
mentioning
confidence: 99%
“…The functional separation of visual processing in upper and lower regions of visual space has been demonstrated using computer-generated three-dimensional virtual environments (VEs; Aguirre & D'Esposito, 1997;Shelton & Gabrieli, 2002). Recently, the lower visual field superiority has also been extended to a spatial memory task by Genzano, Di Nocera, and Ferlazzo (2001), who found that participants were better able to remember the locations of patterned blocks when they had appeared in the lower, as opposed to the upper, visual field during an exposure phase and also that this ability was adversely affected by spatial interference (finger tapping in a spatial sequence), but not by visual interference.…”
mentioning
confidence: 99%